Do new quality productivity forces contribute to wellness tourism resilience? Empirical evidence from China - Wei, Heng; Zhang, Yitong; Hu, Guo (Frontiers in Sports and Active Living, 2025)
Building upon the theoretical foundation of New Quality Productivity Forces (NQPF) and its integration with industrial applications, this study takes wellness tourism as the research carrier and constructs the theoretical framework of “three-dimensional empowerment and four-dimensional evaluation”. Methodologically, We employ an integrated approach combining ArcGIS 10.8 spatial analysis technology with a two-way fixed effects model to empirically examine the spatiotemporal evolution characteristics and driving mechanisms of wellness tourism industries across 30 Chinese provinces from 2014 to 2022. Key findings reveal that: (1) NQPF significantly enhance the resilience of wellness tourism by promoting industrial structure upgrading. (2) Human capital agglomeration, as a critical threshold variable, exhibits a dual-threshold effect on the enabling impact of NQPF, demonstrating a distinct nonlinear leapfrog pattern. This research not only expands the application boundary of NQPF theory in the health field but also provides a reference for the government to formulate health tourism industry policy with both theoretical depth and practical value.